Upaya Kelompok Perempuan Sungai Lemau dalam Merespons Bencana Ekologis di Bengkulu Tengah - Shendy, Shendy; Suminar, Panji; Himawati, Ika Pasca (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Ecological disasters have resulted in environmental damage such as the sedimentation of the Lemau river estuary and abrasion on the coast of Central Bengkulu Regency. The increasingly critical environmental conditions have encouraged the women of Pondok Kelapa Village, who are housewives, to form the Lemau River Women's Group to participate together in efforts to save the environment. This research highlights the efforts made by the Lemau River Women's Group in responding to ecological disasters and environmental damage in Pondok Kelapa II Village, Central Bengkulu Regency, Bengkulu Province. A qualitative research method with a descriptive approach was chosen to explain the efforts made by the Lemau River Women's Group in advocating for environmental protection as a response to influence public policy and save the village's coastal area. The research data were collected through non-participant observation, in-depth interviews, and documentation, and then the data analysis stage was carried out. The results showed that the efforts made by women's groups in responding to ecological disasters include: non-litigation environmental advocacy as an attempt to influence policies that are environmentally sound and gender-responsive are still being fought for by women's groups today, other initiatives are efforts to adapt and mitigate ecological disasters carried out by groups by switching jobs to find alternative sources of income or economy from the previous way of utilizing marine products, then some initiatives have been carried out by women's groups by planting mangroves which aim to be an ecosystem rehabilitation action for further response to mitigate disasters and save the village coastal area. This research concludes that environmentally conscious women have become a pressure group for public policies that are not ecologically sound and have an impact on the ecological, and socio-economic conditions of the community. Women's groups are also at the forefront of responding to ecological disasters and environmental damage through disaster adaptation and mitigation efforts.